Synthesis of ce/mgo catalysts for direct oxidation of hibiscus cannabinus stalks to vanillin - Anuar, N.A.S.I.K. (MDPI, 2021)
One possible method of producing vanillin from biomass is through controlled oxidation of lignin. Direct oxidation of kenaf stalks was chosen without having to separate the cellulose and hemicellulose components from the lignocellulosic biomass. This makes the process greener, as well as saving time. In this paper, Ce/MgO catalysts were developed for oxidation of kenaf stalks and kenaf lignin under microwave irradiation. The catalysts were characterized for their physicochemical properties using XRD and N2 adsorptionâdesorption isotherms. The synthesized MgO showed the presence of diffraction peaks assigned to cubic MgO while the 30Ce/MgO catalysts showed the presence of cubic fluorite of CeO2. N2 adsorptionâdesorption isotherms showed that all catalysts possess Type III isotherm according to IUPAC classification, indicating a nonporous structure. All catalysts were tested for direct oxidation of kenaf stalks under 300 W of microwave irradiation using H2O2 as the oxidizing agent at pH 11.5 and temperatures between 160 and 180 Â°C for 10â30 min with 5â15 catalyst loading. The highest vanillin yields of 3.70 and 2.90 for extracted lignin and direct biomass oxidation were achieved using 30Ce/MgO-48. In comparison, 7.80 and 4.45 were obtained using 2N of NaOH homogeneous catalyst for extracted lignin and direct biomass, respectively, at 170 Â°C for 20 min. The reusability test shows that 30Ce/MgO can be used up to three cycles without significant loss in catalytic activity. Other compounds detected were 4-vinylguaiacol, syringol and syringaldehyde. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.